Chinese in the Philippines a bibliography - See, Chinben; See, Teresita Ang (China Studies Program, De la Salle University, 1990)
This bibliography aims to provide a timely guide to existing studies and articles on the Chinese in the Philippines. It points out the principal problematic areas of the Chinese community. This book does not pretend to be exhaustive but it is unquestionably representative and adequate.